Management of children's fever by parents and caregivers: Practical measurement of functional health literacy. (December 2014) - Emmerton, Lynne; Chaw, Xin Yao; Kelly, Fiona; Kairuz, Therese; Marriott, Jennifer; Wheeler, Amanda; Moles, Rebekah
Functional health literacy is founded on general and numerical literacy and practical skills and is required for the appropriate and effective management of health symptoms in children. This study aimed to assess the health literacy skills of parents and caregivers of preschool-aged children, using a progressive scenario describing a child with fever and presenting tasks relating to selection of a medicine and hypothetical dosing of their child. Participants ( n = 417) from 33 childcare- and health-related sites in Sydney, Brisbane, Melbourne and Auckland completed the study. Participants' responses were largely appropriate regarding actions in response to worsening symptoms, selection of an appropriate product (from a limited range), whereby 84.5% of responses were for a single-ingredient paracetamol product and use of the package directions to state the frequency of dosing (93.1% of frequencies appropriate for paracetamol and 66.7% for ibuprofen). However, in only 50.8% of cases was an appropriate weight-based dose calculated, and doses were not measured to within 10% of the stated dose in 16.7% of cases. Future studies should focus on skill development via educational campaigns for parents and caregivers.